The price of corporate professionalisation: analysing the corporate capture of professions in the UK. (November 2013) - Paton, Steve; Hodgson, Damian; Muzio, Daniel
Abstract : Recent debates on the organisation of expert labour focus upon either the growing dominance of managerialism over traditional professions or the unwillingness/inability of new expert occupations to professionalise. Such arguments frequently disregard expert occupations that continue to deliberately pursue professionalisation to improve their status and influence in organisations and wider society, and therefore overlook the consequences of contemporary professionalisation for expert labour. Here we critically examine one 'corporate profession', project management in the UK, which has pursued 'corporate professionalisation' by renegotiating relationships with the state, individual members and private corporations, with some degree of success. Combining documentary analysis and interviews with professional association officials and practising project managers, this article analyses the pressures behind the corporate professionalisation strategies of this expert occupation, assessing the impact of moves towards a new model of corporate professionalism that marginalises the interests of professionals while embracing employer agendas.